Studying the role of glycan-based biomarkers in cancer : Towards prognostic and therapeutic applications - Lourenço, Rita Adubeiro (2024)
Glycosylation is a complex post-translational modification that impacts most proteins in the human body and is critical for several biological processes. Disruptions in glycosylation are often associated with diseases, particularly cancer, where altered glycan structures drive tumour development and progression. One key alteration is the increase in sialylated glycans like the abnormal sialyl-Tn (STn), typically absent in healthy tissues, making it a promising cancer biomarker and therapeutic target. However, the exact role of STn in cancer progression is still unclear and remains under active investigation. This thesis aimed to clarify the role of STn in cancer, more specifically in triple-negative breast cancer (TNBC) and colorectal cancer (CRC). A systematic review of the literature revealed that STn is generally associated with poor survival. However, its prognostic value varies across cancer types and cohorts. Mucins, along with proteins like CD44 and beta 1 integrin (ITGB1), were identified as key carriers of STn in cancers, all of which are involved in tumour progression. In TNBC, only ~25 % of the cases express STn. This subgroup is associated with reduced survival and with an immunosuppressive environment. STn shows a negative association with the c-Myc, despite promoting higher cell proliferation in vitro. In CRC, STn expression is present in most cases and correlated with important molecular features such as microsatellite instability (MSI) and with glycosylation-related genes, such as the ST6GALNAC1 gene, which explains the expression of STn and correlated with the consensus molecular subtype 3 (CMS3). Additionally, this work presents the development of an interactive platform integrating visualisation tools of glycomic and glycosylation-related transcriptomic data from cancer cell lines and tissues. It provides a tool to visually explore glycosylation traits, which significantly contributes to cancer glycosylation research and accelerates the identification of glycan-based biomarkers that can be used in the clinic. Overall, this work's findings elucidate the impact of STn on cancer progression, rein-forcing its significant but complex role as a cancer biomarker for prognostic and targeted therapeutic purposes.